(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes the peculiar features of American short stories written by American writers. An article begins with the emergence of the short story genre in American literature, its widespread use up to the present time, the writers who wrote in this genre, their great contribution to American short story writing, as well as the concept of the American dream in their stories. In addition, we explore the diversity of themes and ideas, the ability to adequately reflect irony and parody in American stories.